2020
DOI: 10.2337/dc20-0388
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits and Harms of Gastric Bypass Surgery in Obese Individuals With Type 1 Diabetes: A Nationwide, Matched, Observational Cohort Study

Abstract: OBJECTIVE To study the potential long-term benefits and possible complications of bariatric surgery in patients with type 1 diabetes (T1D). RESEARCH DESIGN AND METHODS In this register-based nationwide cohort study, we compared individuals with T1D and obesity who underwent Roux-en-Y gastric bypass (RYGB) surgery with patients with T1D and obesity matched for age, sex, BMI, and calendar time that did not undergo surgery. By l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…29 The recent Swedish study showed that bariatric surgery in obese individuals with type 1 diabetes reduced the incidence of cardiovascular mortality. 21 In our cohort, bariatric surgery had beneficial effects on blood pressure, lipid profile, and total daily insulin dose per kilogram of body weight. Although we did not estimate it directly, it seems likely that these changes would be associated with a reduction in insulin resistance.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…29 The recent Swedish study showed that bariatric surgery in obese individuals with type 1 diabetes reduced the incidence of cardiovascular mortality. 21 In our cohort, bariatric surgery had beneficial effects on blood pressure, lipid profile, and total daily insulin dose per kilogram of body weight. Although we did not estimate it directly, it seems likely that these changes would be associated with a reduction in insulin resistance.…”
Section: Discussionmentioning
confidence: 67%
“…21 Previous studies have tested the use of adjunctive therapies to help with weight loss in patients with type 1 diabetes, including metformin, glucagon-like peptide-1 receptor agonists and sodiumglucose cotransporter-2 inhibitors, all with limited and temporary success. [22][23][24] The improvement in glycaemic control in the study cohort was modest and comparable to that previously reported, 12,13,21 albeit in the context of a marked and significant reduction in daily insulin requirement. Possible mechanisms for the improvement in glycaemic control include reduced caloric intake, reduction in obesity-associated insulin resistance and reduction in lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations